2002
DOI: 10.1021/ja0125117
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Covalently Appended Quinolones on Termini of DNA Duplexes

Abstract: Quinolones are gyrase inhibitors that are widely used as antibiotics in the clinic. When covalently attached to oligonucleotides as 5'-acylamido substituents, quinolones were found to stabilize duplexes of oligonucleotides against thermal denaturation. For short duplexes, such as qu-T*GCGCA, where qu is a quinolone residue and T is a 5'-amino-5'-deoxythymidine residue, an increase in the UV melting point of up to 27.8 degrees C was measured. The stabilizing effect was demonstrated for all quinolones tested, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 44 publications
6
85
0
Order By: Relevance
“…Nevertheless, optimized cap ogOA does feature a phosphodiester linker, a five-membered ring, and amide linkages, much like the composite T*OA cap identified for DNA:DNA duplexes, in which T* stands for a 5'-amino-5'-deoxythymidine residue with an amide link to oxolinic acid (OA). [40] Our results emphasize the importance of the linker. Although the strong propensity of quinolones to stack on nucleobases appears to be a driving force, unless the linker allows it to do so without disrupting weak base pairs (and contributes some binding affinity itself), no increase in sequence selectivity is imposed upon hybridization probes.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Nevertheless, optimized cap ogOA does feature a phosphodiester linker, a five-membered ring, and amide linkages, much like the composite T*OA cap identified for DNA:DNA duplexes, in which T* stands for a 5'-amino-5'-deoxythymidine residue with an amide link to oxolinic acid (OA). [40] Our results emphasize the importance of the linker. Although the strong propensity of quinolones to stack on nucleobases appears to be a driving force, unless the linker allows it to do so without disrupting weak base pairs (and contributes some binding affinity itself), no increase in sequence selectivity is imposed upon hybridization probes.…”
Section: Discussionsupporting
confidence: 51%
“…[40] UV melting experiments: Melting curve experiments used sodium phosphate buffer (10 mm) at pH 7 with NaCl concentrations of 150 mm or 1 m and strand concentrations of 1.0 mm for duplexes of 1 and 2 or 1.5 mm (each strand) for duplexes of 15-18. For each sample, at least four curves from 5 to 80 8C were measured at a heating or cooling rate of 1 8C min À1 .…”
Section: Methodsmentioning
confidence: 99%
“…It has also been shown that by appropriately attaching multiring fused systems [4-desmethylwyosine (39), quinolones (38), phenazinium (51,52), pyrene and phenanthrene (42), phenylurea and naphthylurea (41), cholic acid (53, 54) and a 5′-acylamido FIGURE 2: Definition of the distances used to calculate the hydrogen bond screening value. The schematic view of the X-Y plane of a G-C closing basepair (black) and a G dangling end (blue) shows the distances 1a, 1b, 2a, 2b, 3a, and 3c used to define the extent of screening.…”
Section: Resultsmentioning
confidence: 99%
“…The "wobble hypothesis" [4] has helped to explain the degeneracy of the genetic code, but does not allow for more than qualitative predictions outside the ribosome, and the fidelity of base pairing, particularly at the termini, remains difficult-to-predict. [5] Ligands that enhance stability and base-pairing fidelity at the termini when covalently attached to one of the duplex-forming strands have been identified, but the structural diversity among these ligands, ranging from steroids [6] to aromatic systems like quinolones, [7,8] and stilbenes, [9,10] has made it difficult to draw general conclusions.…”
Section: Introductionmentioning
confidence: 99%